Repositioning dalam Meningkatkan Kesadaran Merek (Brand Awareness): Studi Kasus Repositioning Merek Batik Semar - Suyanto, Budi (Magenta | Official Journal STMK Trisakti, 2018)
Indonesia is a country rich in diversity batik spread across the country ranging from batik Cirebon, Pekalongan, Solo, Yogyakarta to Ubud in eastern of Indonesia. The entire batik has high economic potential not only domestically but also abroad. One of the main perpetrators of batik industry in Indonesia Batik Semar was founded by Somadi and Niniek Elia Kasigit 1947 as the brand's first batik in Indonesia. With the growth of the batik industry is very high, as well as the situation of intense competition resulted in Batik Semar keeps getting overlooked for the Batik Semar should have the right strategy and interesting to be able to continue to be people awareness. Batik Semar pursuing a strategy of repositioning from a old brand be able to build a brand that is traditional and cotemporary potential of batik as the nation's cultural heritage and develop it in the global fashion industry.